Full-Length Transcriptome Sequencing Analysis of Differentially Expressed Genes and Pathways After Treatment of Psoriasis With Oxymatrine - Xue, Xiaoxiao; Yu, Jiayu; Li, Cheng; Wang, Fang; Guo, Yatao; Li, Yongwen; Shi, Huijuan (Frontiers in Pharmacology, 2022)
Psoriasis is a recurrent chronic inflammatory skin disease. Most current treatments have side effects, and their curative effects are limited. Oxymatrine can effectively improve severe plaque psoriasis with mild adverse reactions. We explored the genes and pathways affected by oxymatrine in the treatment of psoriasis. Patients with severe plaque psoriasis were treated with oxymatrine. Their lesions were sequenced by full-length transcriptomics. After the differentially expressed genes in psoriatic lesions were identified, oxymatrine-treated patients and healthy controls were compared, and functional annotation, protein–protein interaction network analysis and immunohistochemistry were performed. Both Psoriasis Area and Severity Index (PASI) and Body Surface Area (BSA) score recovered significantly 16 patients (all P <0.001). The number of differential genes in patients before vs. after oxymatrine treatment were 4232 and 4105 differential genes between patients before oxymatrine treatment and normal control group (P < 0.01, |log2 fold change, (FC)| >1.5). However, most of the differential genes recovered significantly after oxymatrine treatment, and there were only 650 differential genes compared with the normal control group (P < 0.01, |log2FC|> 1.5). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that there were 64 pathways before vs. after oxymatrine treatment (P < 0.05). Among all the restored pathways, the improvement of IL-17 signal pathway was the most significant (P=1.18E-06). Protein interaction analysis was carried out on the 205 differentially expressed genes (DEGs) coexpressed in 5 patients before vs. after oxymatrine treatment to identify the gene loci of oxymatrine action (P < 0.05, FC >1.5). Cyclin dependent kinase 1(CDK1) and cyclin B1 (CCNB1) are related to mitosis and affect cell proliferation. After oxymatrine treatment, the expression of these two genes recovered significantly. We conclude that oxymatrine could change the abnormal expression state of some genes and pathways in patients with psoriasis. Multipathway and multitarget therapy can greatly ameliorate abnormalities in genes and pathways and effectively treat psoriasis. Among the differentially expressed genes, the proliferation-related genes CDK1 and CCNB1 may be important targets for oxymatrine in the treatment of psoriasis. These findings open up a new strategy for the treatment of psoriasis.